2013
DOI: 10.1186/1916-0216-42-16
|View full text |Cite
|
Sign up to set email alerts
|

Serum biomarkers of papillary thyroid cancer

Abstract: ObjectiveTo identify serum biomarkers of papillary thyroid cancer.MethodsProspective analysis was performed of banked tumor and serum specimens from 99 patients with thyroid masses. Enzyme-linked immunosorbent assay (ELISA) was employed to measure levels of five serum proteins previously demonstrated to be up-regulated in papillary thyroid cancer (PTC): angiopoietin-1 (Ang-1), cytokeratin 19 (CK-19), tissue inhibitor of metalloproteinase-1 (TIMP-1), chitinase 3 like-1 (YKL-40), and galectin-3 (GAL-3). Serum le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
5
25
1
1
Order By: Relevance
“…Data obtained during this study are consistent with those of previous studies by Saussez (32), Gang (35) and Makki et al (36), and serum Galectin-3 levels markedly increased in papillary thyroid malignancies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Data obtained during this study are consistent with those of previous studies by Saussez (32), Gang (35) and Makki et al (36), and serum Galectin-3 levels markedly increased in papillary thyroid malignancies.…”
Section: Discussionsupporting
confidence: 93%
“…Maki et al (36) have revealed markedly higher serum Galectin-3 levels in patients with papillary cancer compared with that in the control group.…”
Section: Discussionmentioning
confidence: 95%
“…Galektin-3 β galaktozidaz bağlayan spesifik bir proteindir. Kanser gelişimindeki rolü tam olarak bilinmemekle birlikte Gal-3 ün artmış ekspresyonunun tümör hücrelerinin adhezyon ve motilitelerini değiştirerek metastaz potansiyelini artırdıkları bildirilmektedir [11]. Birçok araştırma sonuçlarına göre Gal-3 özellikle papiller tiroid kanserlerinde olmak üzere differensiye tiroid kanserlerinde pozitiftir.…”
Section: A İmmünohistokimyasal Belirteçlerunclassified
“…Accumulating evidences have revealed an elevated concentration of serum galectin-3 in various cancers including breast 16) , colorectal 17,18) , stomach 19) , lung 16) , bladder 20) , head and neck 21) , liver 22) , melanoma 23) , pancreatic 24) , and thyroid [25][26][27][28][29] . As for thyroid cancer, Yılmaz et al reported that serum galectin-3 level was a significant biomarker to distinguish thyroid cancer from benign nodules 25) .…”
Section: Introductionmentioning
confidence: 99%
“…As for thyroid cancer, Yılmaz et al reported that serum galectin-3 level was a significant biomarker to distinguish thyroid cancer from benign nodules 25) . However, the significance of circulating galectin-3 as a biomarker is still controversial [26][27][28][29] . Recently, Chen et al reported that galectin-3 induces secretion of metastasis-promoting cytokines, such as interleukin (IL)-6, granulocyte colony-stimulating factor Circulating galectin-3 correlates with angiogenetic factors, indicators of nutritional condition and systemic inflammation in patients with thyroid cancer Tatsuo Shimura 1) , Masahiko Shibata 2) , Kenji Gonda 2) , Takahiro Nakajima 3) , Shun Chida 3) , Masaru Noda 3) , Satoshi Suzuki 4) , Izumi Nakamura 4) , Keiichi Nakano 4) , Toshihiko Fukushima 4) , Shinichi Suzuki 4) (G-CSF), granulocyte macrophage colony-stimulating factor and soluble intercellular adhesion molecule-1 (sICAM-1) 30) .…”
Section: Introductionmentioning
confidence: 99%